Menerapkan Konsep Ekonomi Berbasis Teknologi Blockchain Menggunakan Non-Fungible Token pada Game NFTSmith - Bakhtiar Bakhtiar; Fajar Darmawan; Handoko Supeno (Query: Journal of Information Systems, 2022)
The increased number of players and transactions in online games causes third-party markets to carry out buying and selling transactions, the security factor from the open market that determines the number of frauds ranging from between players to service providers. The methodology consists of four stages: understanding the problem in order to find various approaches to solving it, collecting data for relevant theories, system design (which includes blockchain system design and blockchain infrastructure) that is then translated into design so that the implementation can be clearly seen in NFTSmith, and system development. A blockchain-based economy eliminates the need for third-party transactions, and on-chain transactions can be carried out in a decentralized mannerKeywords: Blockchain, Decentralized Marketplace, Game Economy, Non-Fungible Token, Market